2,6-Diaryl-4-Indolylpyridines as Novel 5-LOX Inhibitors - Berihu Tekluu; Kumari Yettula; Sunanda Kumari Kadiri; Siddaiah Vidavalur (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
3-Substituted indole is a privileged structural motif found in many biologically active compounds and natural products. 3-Substituted indole derivatives exhibit several biological activities such as antibacterial, anti-inflammatory, antitumor, anticancer, anti-hypertensive, anti-depressant, and antiviral activities. The study aims to synthesize a series of 2,6-diaryl-4-indolylpyridines from substituted acetophenones and 1H-indole-3-carbaldehydes using ammonium acetate as a nitrogen source in the presence of acetic acid and 5-LOX activities of several 2,6-diaryl-4-indolylpyridines. A series of 2,6-diaryl substituted-4-indolylpyridines has been synthesized from indole-3-carboxaldehyde and acetophenones, and all the compounds have been characterized by spectroscopic techniques. 5-Lipoxygenase enzyme inhibitory activities were performed for all the compounds. 1H-Indole-3-carboxaldehyde and 5-bromo-1H-indole-3-carboxaldehyde were prepared from indole using phosphorus oxychloride in DMF. The reaction of indole-3-carboxaldehyde (1a-b) with substituted acetophenones (2a-i) in the presence of ammonium acetate in acetic acid at reflux conditions furnished 2,6-diaryl-4-indolylpyridines (3aa-3bf) in 63-84% yield. Based on this protocol, 14 derivatives of all the compounds were purified by column chromatography on silica gel. The chemical structures of the target compounds were confirmed by 1H NMR, 13C NMR, and MS spectra Among the 2, 6-diaryl substituted-4-indolylpyridine derivatives, 3ad and 3aa showed good activity.